Cancer survivorship: existential suffering - Venke Ueland (Taylor & Francis Group, 2021)
Purpose This study aimed to explore and describe existential experiences after cancer treatment. Method An exploratory phenomenological hermeneutical design was used following in-depth interviews with 21 people. Results The study revealed experiences of multifaceted suffering in the form of limitations in everyday life, inner struggles, and bearing the burden alone. Conclusions Existential suffering after cancer treatment was revealed as like being in a process of transition, in an intermediate state, as moving between suffering and enduring, and alternating between alienworld and homeworld. A new and broader professional perspective is needed to establish rehabilitation services based on multifaceted experiences of suffering. This means a shift in focus from biomedical symptoms towards understanding of existential meaning for the person.